The Impact of Using Social Media as a Learning Tool on the Development of Elementary School Students' Social Skills - Muthmainnah (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The use of social media as a learning tool is increasingly widespread in elementary education. This study aims to evaluate the impact of social media use on the social skills of elementary school students. The use of social media as a learning tool at SD Negeri 2 Wameo offers many benefits, there are significant gaps in its implementation. This study uses Qualitative Research Type. In addition, interviews with teachers and classroom observations were also conducted to obtain additional data. By collecting and analyzing existing theories, this study will build a strong conceptual framework to support the findings and data analysis. The results of the study show that the use of social media in learning at SD Negeri 2 Wameo significantly improves students' social interaction, adaptability, communication skills, and empathy development. Although it offers many benefits, it is important to manage the use of social media wisely to avoid risks and ensure that this platform supports a positive and effective learning environment. Although it offers many benefits in students' social development, the use of social media as a learning tool requires wise management.